Arginine-specific repression in Saccharomyces cerevisiae: kinetic data on ARG1 and ARG3 mRNA transcription and stability support a transcriptional control mechanism. - Crabeel, M (1990)
A specific repression mechanism regulates arginine biosynthesis in Saccharomyces cerevisiae. The involvement of regulatory proteins displaying DNA-binding features and the location of an operator region between the TATA box and the transcription start of the structural gene ARG3 suggest that this mechanism operates at the level of transcription. A posttranscriptional mechanism has, however, been proposed to account for the conspicuous lack of proportionality between ARG3 mRNA steady-state levels (as determined by Northern [RNA] assays; F. Messenguy and E. Dubois, Mol. Gen. Genet. 189:148-156, 1983) and the cognate enzyme activities. In this work, we have analyzed the time course of the incorporation of radioactive precursors into ARG1 and ARG3 mRNAs and the kinetics of their decay under different regulatory statuses. The results (expressed in terms of relative mRNA levels, relative transcription rates, and mRNA half-lives) give the picture expected from a purely transcriptional control. A similar analysis of expression of the gene CPA1, for which a translational regulation by arginine has been clearly demonstrated (M. Werner, A. Feller, F. Messenguy, and A. Piérard, Cell 49:805-813, 1987), indicates that this gene is also partly regulated at the transcriptional level by the ARGR repressor system. Moreover, the half-life of CPA1 mRNA is reduced twofold in the presence of excess arginine; we suggest that this could be inherent in the mechanism of translational regulation of CPA1.